Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.3 - Adding and Subtracting Rational Expressions with the Same Denominator and Least Common Denominator - Exercise Set - Page 507: 9



Work Step by Step

$\dfrac{5x^{2}+4x}{x-1}-\dfrac{6x+3}{x-1}$ Evaluate the substraction of the two rational expressions: $\dfrac{5x^{2}+4x}{x-1}-\dfrac{6x+3}{x-1}=\dfrac{(5x^{2}+4x)-(6x+3)}{x-1}=...$ $...=\dfrac{5x^{2}+4x-6x-3}{x-1}=\dfrac{5x^{2}-2x-3}{x-1}=...$ Factor the numerator and simplify: $...=\dfrac{(5x+3)(x-1)}{x-1}=5x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.